A global view of gyroporus: Molecular phylogenetics, diversity patterns, and new species - Davoodian, Naveed; Bergemann, Sarah E.; Hosaka, Kentaro; Raspé, Olivier; Bougher, Neale L.; Fechner, Nigel A.; Henkel, Terry W.; Gelardi, Matteo; Soytong, Kasem; Naseer, Arooj; Ortiz-Santana, Beatriz; Baroni, Timothy J.; et al. (My University, 2018)
Gyroporus (Gyroporaceae, Boletales) is a highly diverse genus of poroid ectomycorrhizal mushrooms with a nearly worldwide distribution. Previous attempts to unravel the diversity within this genus proved difficult due to the presence of semicryptic species and ambiguous results from analysis of ribosomal RNA markers. In this study, we employ a combined morphotaxonomic and phylogenetic approach to delimit species and elucidate geographic and evolutionary patterns in Gyroporus. For phylogenetic analyses, the protein-coding genes atp6 (mitochondrial adenosine triphosphate [ATP] synthase subunit 6) and rpb2 (nuclear second largest subunit of RNA polymerase II) were selected based on their utility in studies of Boletales. We infer several distinct clades, most notably one corresponding to G. castaneus as a speciose Northern Hemisphere group, another unifying G. cyanescens and like entities, and a third group unifying G. longicystidiatus and a New World sister species. Also notable is the recovery of a sister relationship between the cyanescens and longicystidiatus clades. We formally describe five new species of Gyroporus, outline a number of provisional species, and briefly discuss distributional patterns. This study provides an important scaffold for future work on this well-known but poorly understood genus of fungi.
Keywords: 5 new taxa; Atp6; Boletales; Ectomycorrhizal fungi; Rpb2; Systematics